ANALISIS YURIDIS KONTRAK OLEIN PADA PERDAGANGAN BURSA BERJANGKA JAKARTA - Armansyah Siregar; Bismar Nasution; Alvi Syahrin; Sanwani Nasution (USU LAW JOURNAL, 2016)
ABSTRACTThe development of the world economy into the modern era, in which various forms of financial business is growing rapidly, futures exchange can be used as a modern institution of agricultural commodity trading, commodity futures or commodity exchange is present in hopes of helping to run the risk of price fluctuations that occur. Indonesia as a country that has a variety of commodities requiring a transaction mechanism that is organized, orderly, fair, effective, and efficient, the Jakarta Futures Exchange (BBJ) was formed to facilitate the means of transaction between buyers and sellers meet in a futures contract with a brokerage firm stock exchange members. The setting of the type-olein contract to be traded and regulated in the Code Jakarta Futures Exchange. Based on the results of research to understand the procedures for futures transactions, the transaction can only be traded on an exchange, and traded by parties who have a license / business from BAPPEBTI, and conducted in accordance with the rules and regulations applicable stock exchange, as well as setting the futures contracts to be traded Regulation and Discipline of the Jakarta Futures Exchange, futures contracts have a standard form contracts based on the specifications that have been established such as the quality, type and clear pricing. Futures contract has a clearinghouse that guarantees fully to completion transksi on futures contracts. The terms of the payment made in the form of futures trading margin. Futures contract has a trading and closing hours every day (daily settlement) and any futures position can be closed at any time.Keywords: contract, olein, trading, Jakarta Futures Exchange.